Um estudo sobre o envolvimento das empresas privadas de Uberlândia nas questões ambientais - Garcia, Paulo Teodoro (2007)
The industrial activities are responsible for a great part of the global impacts on the environment. Some of the main questions related to these problems are: the heating of the temperature of the land, the destruction of the ozone layer, the pollution of waters, the degradation of the ground and the loss of biodiversity. The aim of this research was to investigate the involvement of the Uberlandia s private companies, with the environment education. To reach this objective a questionnaire was sent to 63 companies of Uberlandia focusing: activities exerted for the company versus environment damages; existence of programs or projects financed by the company directed towards the environment preservation; who is the target public of these projects; who demands these projects; which activities are expected in these projects; who are the involved professionals in these projects; which bibliography is used as reference; explanation for the absence of investments in this sector; interest in implement them in case they still do not exist; which activities the company would like to be involved with; which are the barriers for the development of activities of environment education in the company and which contribution the environment education can add to the businesses of the company. Twenty eight companies answered to the questionnaires, and their answers evidenced that, even though to invest in environment projects is not a priority for the city companies, possibilities of investments in this area exist, a result that stimulates the environment educators who act in schools, in parks and other informal spaces to look for the companies in the direction to search for partnerships for the development of projects in the city, aiming the environment preservation.